James Watt, chemist [ understanding the origins of the steam age - Miller, David Philip (Science and culture in the nineteenth century, 2009)
This text examines James Watt's illustrious engineering career in light of his parallel interest in chemistry, arguing that Watt's conception of steam engineering relied upon chemical understandings.